Increasing access to higher education: Reflections on a border crossing curriculum designed for an enrichment programme for talented high school learners - Brenner, Elisabeth (South African Journal of Higher Education, 2016)
Curricula in programmes aiming to increase access to higher education for learners from disadvantaged communities often need to provide maximum benefit within a short contact period. With this in mind, a new subject, Molecular Literacy, was introduced into a residential enrichment programme for talented grade 10 - 12 learners who attended for 2 weeks annually. This curriculum, which included concepts from different subject areas, was designed to encourage learners to think more broadly and outside the narrow confines of school subjects. The longitudinal progression of content knowledge was coherent, the cognitive demand increased each year and learners were encouraged to question and think critically through the use of various pedagogies. I argue that a constructed subject area that crosses borders can, with careful curriculum design, play a valuable role in assisting learners to acquire the social and cultural capital to gain access to and succeed in the higher education environment.